PENINGKATAN KEMANDIRIAN DAN PRESTASI BELAJAR MATEMATIKA DENGAN PENDEKATAN PROBLEM BASED LEARNING (PBL) DI KELAS VII E SMP N 15 YOGYAKARTA - Margaretha Madha Melissa (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2016)
The aims of this research is to increase achievement and self-regulated mathematics learning trought Problem-Based Learning (PBL) approach in class VII E of Junior High School 15 Yogyakarta. This is classroom action research that use Kemmis and Mc Taggart model consists of four stages: planning, action, observation, and reflection. The subjects were 34 students from class VII E of Junior High School 15 Yogyakarta. The research instruments were students’ self-regulated learning questionnaire, achievement tests, and observation sheets for learning implementation. The data analysis technique is descriptive analysis. This research were succes if more than 65% of pupils in high category and 35% of pupils in very high category of self-regulated mathematics learning and more than 70% of students pass mathematics achieve test. Based on the results of students’ self-regulated learning questionnaire showed increased percentage of students' self-regulated. In the initial conditions, 20% of students reached the medium category, 71% of students in the high category, and 9% of pupils achieve very high category. In the first cycle, 73% of students achieve high category and 27% of students at very high category. In the second cycle, 59% of students achieve high category and 41% of students at very high category. Based on the results of mathematics achievement test, in the initial conditions only 2.94% of the students passed mathematics achieve test with an average value is 30, the first cycle 94.12% students passed the test with an average is 85, and the second cycle 82.35% students passed the test with an average is 77. Therefore, it can be concluded that the problem-based learning (PBL) approach can increase the students’ self-regulated learning and mathematics achievement of class VII E in Junior High School 15 Yogyakarta. Keyword: PBL approach, self-regulated learning, mathematics achievement